Top Answer

I Don't know. go search some were else LOSERS!

🙏

1🤨

1😮

1😂

1Loading...

8x-4

2x squared plus 2x plus xy plus y or 2x(x+1) + y(x+1) or (x+1)(2x+y)

(2x + 1)(2x + 1) or (2x + 1)2

x=1

x = 0

4x + 1 = 2x + 5 4x + 1 - 2x = 2x + 5 - 2x 2x + 1 = 5 2x + 1 - 1 = 5 - 1 2x = 4 2x/2 = 4/2 x = 2

4x2 + 12x + 5 = 4x2 + 2x + 10x + 5 = 2x(2x+1) + 5(2x+1) = (2x+1)(2x+5)

OK. 4x2 + 4x + 1 = (2x + 1)2

2x2 + 2x = 2x(x+1)

4

x=5.54x+1= 2x+12-1 -14x=2x+11-2x -2x2x=11/2 /2x=5.5

14

2x+5+x-1=3x+4

x2+2x+1 = (x+1)*(x+1)

8x2 + 2x - 1 = (4x - 1)(2x + 1).

(2x + 1)(2x + 1) or (2x + 1)2 so x = -0.5

4x-1=2x+1

Y = 2x + 1

(2x + 3)(x + 1 ) = 2x^2 +5x +3

(-2x2 + x + 1) / (x - 1) = (-2x - 1)(x - 1)/(x - 1) = -2x - 1

8x2 + 2x - 1 = 8x2 + 4x - 2x - 1 = 4x(2x + 1) - 1(2x + 1) = (4x - 1)(2x + 1)

4x3+10x2+2x+5= (2x+5)(2x2+1)

-2x+2

I'm answering this based on the way you wrote it. If you meant something different, please substitute words where necessary. x2-2x+4+2x+1-x62+5=2x-2x+4+2x+1-62x+5=-60x+10

2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2